SCIENTIFIC SIGNIFICANCE OF EDUCATIONAL PRINCIPLES AND LAWS IN TEACHING (American Journal of Pedagogical and Educational Research, 2023)
The article highlights the principle of regularity and consistency in ensuring educational effectiveness, the importance of the principle of scientific and understandable educational material, the role of the principle of associating theory with practice in teaching, ways to increase the awareness and creative activity of learners.